Relación entre las actividades agropecuarias y el valor de los servicios ambientales en diez comunidades rurales de Manabí - Vélez Sabando, Luisa María (2022)
The objective of the research was to evaluate the relationship between agricultural activities and the value of environmental services in ten rural communities in Manabí province: Garrapata, San Pablo de Tarugo, La Piñuela, Las Cañitas, La Pastora, Cabello de Adentro, Sarampión, Julián, Agua Fría and Mocorita. The work was based on bibliographic analysis, field activities and participatory processes with 333 heads of household. The development of the research included: 1) socioeconomic and agricultural diagnosis through cartography, statistics, surveys and on-site observations; 2) valuation of environmental services using the contingent method; and 3) design of a management plan. The results showed that farming is the main economic activity (62.64%) and that a young adult population predominates (mean: 29 years). Eighteen agricultural and livestock activities were identified, with cocoa cultivation (1,500 ha) being the most important, followed by cattle breeding (>1,800 ha), with the latter having the greatest negative impacts on 11 environmental components. Thirty-two environmental services were identified, with the provision of cultivated food being the most valued (100%). The average WTP was 4.15 USD/month as payment for environmental services (30,178 USD/year). The relationship between agricultural activities and environmental services is significant (p<0.05), despite the lack of ecological knowledge, especially those of regulation and support. The management plan proposes a broad vision of participatory governance and strengthening of environmental public policies. I concluded that agricultural activities are significantly (p<0.05) related to the value of environmental services in the rural communities studied.